ANALISIS TEMA DAN FAKTA CERITA NOVEL KETANGGOR DALAM TRILOGI KELANGAN SATANG KARYA SUPARTO BRATA - , ROYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study discusses about theme, fact of a story, and relationship between elements in the Ketanggorâs novel. The analysis used in this study is the structural analysis. Descriptive method used to describe Ketanggorâs novel in terms of structure, analysis method used to analyze the issues that have been described, while the literature study method is by reference to literature sources. Based on the research it can be concluded that the major theme contained in the Ketanggorâs novel is about personâs indecision in determining way of life. Wiradi indecisive in choosing between living with Elok, or divorced with Elok and married to Manik. Minor theme in the Ketanggorâs novel is household problems faced by Wiradi and Elok, promiscuity problem by Manik, loyalty of a husband against his wife and loyalty of a woman against her lover, and Wiradi regrets having divorced Elok and married to Manik. Ketanggorâs novel have straight plot. The story begins when Wiradi come to Surabaya. Then, Wiradi met with Manik, and eventually married with Manik. After Manik died, Wiradi regret it because had been divorced with Elok and choose to marry with Manik. The main characters in the Ketanggorâs novel are Wiradi and Manik, while the subordinate characters are Gatot, Saparas, Mrs. Murakap, Mr. Murakap, Elok, and Wirastuti. Places setting includes Surabaya, Sala, Sragen, Kartasura, and Klaten. Partial time setting includes morning, noon, afternoon, evening, and Sunday. Factual time setting of the Ketanggorâs novel is the period after the revolution. Social setting in the Ketanggorâs novel is associated with Java community life, especially Surabaya.